From the financial crisis to the world economic crisis: The role of inequality - Gustav A. Horn; Katharina Dröge; Simon Sturn; Till van Treeck; Rudolf Zwiener (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
A central cause of the crisis, which the public debate has taken little notice of so far, is the rapid increase of income inequality in many industrialised countries, but also in some emerging economies. In the USA many private households have reacted to stagnating real incomes by increasingly extending their borrowing. This was facilitated by a deregulated financial system. Only thus could private consumption become the main pillar of economic growth in the USA for years. The opposite holds for Germany: here the weak wage dynamics and social spending cuts have induced consumption restraint rather than higher debt, thus causing an extended period of weak domestic growth. High capital exports and a strong (and risky) foreign market involvement of the banking sector were the flip side of the extreme export hikes of the German economy, which were enhanced by weak wage increases. In the current financial crisis the limits of these opposite growth models become evident: both are based on the necessity to compensate the sluggish trend resulting from an increasing income inequality with other sources of demand. These consisted either in increased household borrowing (USA, UK, Spain) or in export- led growth (Germany, Japan, China). – – Eine zentrale Ursache der aktuellen Krise, die von international renommierten Ökonomen betont wird aber in der öffentlichen Debatte in Deutschland noch wenig Beachtung findet, ist die rasante Zunahme der Einkommensungleichheit in vielen Industrieländern, aber auch in einigen Schwellenländern. In den USA haben viele Privathaushalte - unterstützt durch ein dereguliertes Finanzsystem - auf stagnierende Realeinkommen mit einer immer ausgedehnteren Kreditaufnahme reagiert. Nur so konnte der private Konsum über Jahre hinweg zur tragenden Stütze des Wirtschaftswachstums in den USA werden. Anders in Deutschland: Hier haben die schwache Lohnentwicklung und sozialpolitische Einschnitte nicht zu erhöhter Verschuldung, sondern zu Konsumverzicht geführt, dessen Ergebnis eine anhaltende binnenwirtschaftliche Wachstumsschwäche war. Spiegelbild der extremen, durch schwache Lohnzuwächse unterstützten Exportsteigerungen der deutschen Wirtschaft waren hohe Kapitalexporte sowie eine starke (und riskante) Auslandsorientierung des Bankensektors. Mit der aktuellen Krise sind beide Wachstumsmodelle an offensichtliche Grenzen gelangt. Ein Richtungswechsel in der Verteilungspolitik ist eine notwendige Bedingung für die künftige gesamtwirtschaftliche Stabilität der deutschen und auch der globalen Wirtschaft.
urn:nbn:de:101:1-20091104943; Additional information: English version of IMK Report No. 41, translated from German into English by Katja Rietzler. German version: http://hdl.handle.net/10419/106050
Keywords: 330